Design and implementation of a mechanical system for a ground based synthetic aperture radar with automatic antenna pointing: Preliminary results - Ortecho, Daniel (2017)
Special thanks to the CIELO (Cluster of Instruments for Equatorial & Low-Latitude Observations) staff at the Jicamarca Radio Observatory for their technical support, and to Joaquim Fortuny Ph.D. for his guidance in the implementation of this project. Also, We thank FONDECYT for the support to this project through the agreement N?-PIAP-2-P-434-14. The Jicamarca Radio Observatory is a facility of the Instituto Geofísico del Perú (IGP) operated with support from the NSF award AGS-1433968 through Cornell University.